Specific Enhancement of Vascular Endothelial Growth Factor (VEGF) Production in Ischemic Region by Alprostadil - Potential Therapeutic Application in Pharmaceutical Regenerative Medicine - Hajime Inoue; Masaki Aihara; Miyuki Tomioka; Yu-ichi Watabe (Elsevier, 2013)
Alprostadil (lipo-PGE1) is a drug delivery system preparation. This preparation is applied to treat refractory skin ulcers and arteriosclerosis obliterans. We investigated the effects of alprostadil by using the earflap ischemic model. The following results were obtained: 1) Treatment with alprostadil significantly increased the VEGF contents in an ischemic ear; 2) Treatment with alprostadil resulted in strongly expressed VEGF levels only in the ischemic region; 3) Image analysis revealed a significant increase in the number of vessel bypasses and paths after flap creation with alprostadil administration compared to the vehicle-treated ears. The results suggest that it may be possible to apply alprostadil as one device for regenerative medical technology. Keywords:: angiogenesis, alprostadil, regenerative medicine